PENGEMBANGAN SISTEM INFORMASI AKUNTANSI TERINTEGRASI DI PERUSAHAAN YANG SEDANG BERTUMBUH (Studi Kasus Pada PT Molay Satrya Indonesia) - Taufik, Haviz (JURNAL RISET AKUNTANSI JAMBI, 2019)
The objective of this study is to obtain evidence regarding description of the accounting  information  system  and  problems  faced  by  PT  Molay  Satrya Indonesia,   to   analyze   steps   required   for   the   development   of   accounting information system that is integrated in the PT Molay Satrya Indonesia based on   Systems  Development  Life  Cycle  (SDLC), and  challenges  that  may  be encountered  in  the  development  of  integrated  accounting  information  system based on the  Systems Development Life Cycle (SDLC) method. The development method used in this research was Systems Development Life Cycle (SDLC). The study  has  been  done  in  two  stages  which  were  analysis  and  conceptual design. This research was used qualitative case study method with data collection. The  data  analysis  used  in  this  study     field  study,  which  were  included interviewing, observation, and documentation which has been analyzed using data reduction techniques, data presentation, and conclusion. Based on the results of data analysis, information systems owned by PT Molay Satrya Indonesia had not fully integrated between divisions. The next steps required in the development of an integrated accounting system at PT Molay Satrya Indonesia is to identify and evaluate design  alternatives  that  exist.  After  deciding  alternative designs,  PT Molay Satrya Indonesia to decide how to meet the needs of the system. There are three ways to do that is to buy the software, develop their own software, and outsourcing system. Challenges faced in the development of a system that is a challenge to human resources, investment, strategic business, technology infrastructure, and supervision and liability.